Perbandingan Kualitas Website Shopee dan Tokopedia menggunakan Metode Webqual 4.0 (Studi pada Mahasiswa Aktif Universitas Brawijaya) - Vigo Hernando; Diah Priharsari; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The rapid growth in the number of Indonesians who shop online makes e-commerce service providers compete to improve the quality of their services. This is done in order to meet user expectations. On the other hand, the large number of e-commerce in circulation makes users confused about which e-commerce service to use. Therefore, this study aims to compare the quality of the two most popular e-commerce sites in Indonesia, namely Shopee and Tokopedia. This study uses two methods, namely Webqual 4.0 as an indicator of website quality testing and also the Importance Performance Analysis (IPA) method to provide recommendations for priority improvements on each website. Research data obtained from the results of questionnaires to 100 respondents for each e-commerce website. The calculation results found that the Webqual Index (WQI) of Shopee was 0.840 and Tokopedia was 0.844. The results of the Independent Sample T-Test difference test showed that there was no significant difference in the quality of the two e-commerce websites. Furthermore, the results of the analysis using Importance Performance Analysis (IPA) found that on the Shopee website there are 5 indicators with top priority and 4 indicators with low priority for improvement. Meanwhile, on the Tokopedia website, there are 5 indicators with top priority and 5 indicators with low priority for improvement. Other indicators do not need to be improved because the quality has met user expectations.